Pelatihan Pembibitan secara Generatif dan Vegetatif bagi Petani di Kelurahan Setapuk Besar, Kota Singkawang - Emi Roslinda; Farah Diba; Hari Prayogo (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The reduction in forested land in the hills has already affected the Setapuk Besar community. When there were rains with high enough intensity, the Setapuk Besar area often experienced flooding and entered a flood-prone. One way to minimize flooding that occurs is to plant trees in the upstream area, which begins with preparing good seeds for planting. The training aims to provide practical knowledge and skills to the community, especially farmers in Setapuk Besar Village and vegetative agricultural and forestry plantations to plant in yards and hills. The method used the community development practice method, equipped with a participatory and educational approach. Through counseling and training, there are increase participant's knowledge, skill on plant propagation. Plant propagation's expertise and skill positively impact land improvement efforts in hilly areas and community economic empowerment by opening nurseries, especially for superior species in the Setapuk Besar area.